Comprehensive genome-scale CRISPR knockout screening of CHO cells - Sung Wook Shin; Su Hyun Kim; Aghiles Gasselin; Gyun Min Lee; Jae Seong Lee (Scientific Data)
Abstract Chinese hamster ovary (CHO) cells play a pivotal role in the production of recombinant therapeutics. In the present study, we conducted a genome-scale pooled CRISPR knockout (KO) screening using a virus-free, recombinase-mediated cassette exchange-based platform in CHO-K1 host and CHO-K1 derived recombinant cells. Genome-wide guide RNA (gRNA) amplicon sequencing data were generated from cell libraries, as well as short- and long-term KO libraries, and validated through phenotypic assessment and gRNA read count distribution. Additionally, we obtained gRNA amplicon sequencing data from the highly productive recombinant cell populations. By analyzing these datasets, essential genes involved in cell fitness as well as functional target genes associated with therapeutic protein production can be identified. Collectively, our next-generation sequencing datasets, derived from a robust and reliable CRISPR screening method, provide valuable insights into CHO genomic functions, advancing the development of next-generation CHO factories.